Given the functions k(x) = 2×2 − 8 and p(x) = x − 4, find (k ∘ p)(x). (k ∘ p)(x) = 2×2 − 16x + 24 (k ∘ p)(x) = 2×2 − 8x + 8

Question

Given the functions k(x) = 2×2 − 8 and p(x) = x − 4, find (k ∘ p)(x).
(k ∘ p)(x) = 2×2 − 16x + 24
(k ∘ p)(x) = 2×2 − 8x + 8
(k ∘ p)(x) = 2×2 − 16x + 32
(k ∘ p)(x) = 2×2 − 12

in progress 0
Serenity 1 week 2021-11-24T01:05:57+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-11-24T01:06:57+00:00

    (k_ {0} p) (x) = 2x^2 -16x + 24

    Solution:

    Given functions are:

    k(x) = 2x^2 - 8\\\\p(x) = x-4

    To Find: (k_ {0} p) (x)

    By definition of compound functions,

    (k_ {0} p) (x) = k (p (x))

    Substitute p(x) value in x place in k(x)

    (k_ {0} p) (x) = 2(x-4)^2-8\\\\Expand\\\\(k_ {0} p) (x) =2(x^2 -8x +16) - 8\\\\(k_ {0} p) (x) = 2x^2 -16x + 32-8\\\\Simplify\\\\(k_ {0} p) (x) = 2x^2 -16x + 24

    Thus the required is found

    0
    2021-11-24T01:07:04+00:00

    Answer:

    The answer is A. (k o p) (x)=2x^2-16x+24

    Step-by-step explanation:

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )